Impurity states in non-concentric spherical core-shell quantum dot - Bilynskyi, I.; Leshko, R.; Leshko, O.; Terletska, H.; Pazuyk, R.; Voitovych, Kh. (Physics and Chemistry of Solid State, 2024)
It was suggested the model of the non-concentric spherical core-shell quantum dot with hydrogenic impurity. It has been defined that the electron energy spectrum as a function of both an impurity and the core location. The splitting and degeneration of energy levels has been discussed. It is shown that displacing the core of a quantum dot or impurity in opposite directions can lead to alternate splitting and degeneracy of the energy levels of excited states. In certain configurations of arrangements, compensatory effects associated with the partial restoration of spherical symmetry in the field are observed.